Impact of Corporate Income Tax and Value-Added Tax Revenue on Economic Growth in Nigeria: Evidence from an ARDL Bounds Testing Approach - Ifeoma Florence Okpalanwabude (Asha Publishing, 2026)
Nigeria relies heavily on tax revenues, particularly Corporate Income Tax (CIT) and Value-Added Tax (VAT), to fund public expenditure and drive economic growth. However, persistent debates exist regarding the effectiveness of these taxes in stimulating national output, with some studies reporting positive impacts while others suggest negligible or negative effects. This study employed an Autoregressive Distributed Lag (ARDL) framework to examine the impact of corporate income tax revenue and value-added tax revenue on economic growth in Nigeria, controlling for real interest rate and labour force participation. The ARDL bounds testing approach was used to test for long-run cointegration and short-run dynamics among the variables. Where cointegration existed, an error correction model captured both long-run equilibrium and short-run adjustments. Pre-estimation tests included unit root and bounds tests, while post-estimation diagnostics assessed autocorrelation, heteroskedasticity, multicollinearity, and model stability using CUSUM and CUSUMSQ. The findings indicate considerable variability in Nigeria’s macro-fiscal indicators over 1994–2023, with corporate income tax (mean = ₦784.94 billion; SD = ₦1,018.90 billion) and VAT revenue (mean = ₦711.63 billion; SD = ₦927.35 billion) showing high volatility and non-normality (JB = 91.09; 78.64). Unit root tests reveal mixed orders of integration [I(0) and I(1)], validating ARDL use. Bounds testing confirms cointegration (F = 3.66 > 3.49). Long-run results show corporate income tax positively affects growth (β = 0.308, p < 0.01), while VAT has a negative effect (β = –0.00006, p < 0.05). Short-run adjustment occurs at 43%. The error correction term (0.43) suggests a moderate adjustment speed toward equilibrium. In conclusion, improving corporate tax collection and administration can stimulate economic growth, while VAT policies require careful calibration to avoid unintended contractionary effects.